2009
DOI: 10.1177/039139880903201002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Cytokeratin Expression Profiling of Human Oral Mucosa Substitutes Developed by Tissue Engineering

Abstract: In this work we performed a study of cytokeratin (CK) expression profiling on human artificial oral mucosa developed in vitro by tissue engineering at different stages of maturation (from immature to well-developed stages) at the protein and mRNA levels. Human artificial oral mucosa was generated in the laboratory using fibrin-agarose biomaterials. As controls, we used human native normal oral mucosa and embryonic oral tissues. Our results demonstrated that human embryonic oral tissues tended to express CK8 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
4
22
0
1
Order By: Relevance
“…Most of the works focused on the study of AOM have used partial and non‐autologous oral mucosa models to identify epithelial patterns such as DG3, laminin and others . On the one hand, our results confirmed the epithelial phenotype of the bioengineered epithelial layer as determined by the positive expression of pancytokeratin in all AOM samples as we previously demonstrated . On the other hand, laminin expression required 3 wk of in vitro development and the use of air–liquid culture conditions.…”
Section: Discussionsupporting
confidence: 84%
“…Most of the works focused on the study of AOM have used partial and non‐autologous oral mucosa models to identify epithelial patterns such as DG3, laminin and others . On the one hand, our results confirmed the epithelial phenotype of the bioengineered epithelial layer as determined by the positive expression of pancytokeratin in all AOM samples as we previously demonstrated . On the other hand, laminin expression required 3 wk of in vitro development and the use of air–liquid culture conditions.…”
Section: Discussionsupporting
confidence: 84%
“…Additional confirmation that the 3D construct has the features of a lip was found when keratin 10 was not found in the oral section of the construct and keratin 19 was only expressed in the basal layer of the oral section of the construct as seen in Figure 6. These temporary and/or reversible changes in the keratinization profiles of natural and bioengineered oral mucosa constructs have also been previously reported 33 and also have been shown in mice. 34 While our focus was in the fabrication of a construct incorporating labial mucosa cells, a preliminary experiment using cells taken from the alveolar ridge area of the mouth, which is keratinized and similar to skin, indicated that it is also possible to make tissue engineered M/C junctions with skin and keratinized mucosa (Fig.…”
Section: Figsupporting
confidence: 76%
“…When the stromal cells were cultured within the fibrin‐agarose biomaterial, adequate cell integration in the biomaterial was observed as shown by histological and cell viability analyses. These results confirm our previous results suggesting that fibrin‐agarose biomaterials are highly biocompatible ex vivo . Furthermore, the presence of abundant intracellular synthesis organelles as determined by TEM suggests that the cells immersed in the scaffold were not only viable, but also metabolically active, and supports the validness of this biomaterial as an ex vivo cell culturing scaffold.…”
Section: Discussionsupporting
confidence: 90%